Analysis of the Shariah Marketing Strategy in Increasing the Number of Micro Servers Customers at Sharial Bank Indonesia (KCP Aek Kanopan) - Ana Pahira Sipahutar; Tuti Anggraini; Nurul Inayah (Dinasti Publisher, 2024)
In the microfinance marketing strategy of Bank Syariah Indonesia (BSI KCP Aek Kanopan), the marketing mix consists of products, prices, promotions, locations, people, processes, and physical evidence. For this research, the methodology is qualitative, and a data descriptive approach is used. Officials working in the MRM Team Manager section of Bank Shariah Indonesia were interviewed and documented. Microfinance marketing strategies can generate more clients for Sharia Bank Indonesia KCP Aek Kanopan by using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). Microfinance offers competitive margins ranging from fifteen million to two hundred million, and a settlement period of between three and sixty months. With modern facilities, it is strategically located in the heart of Aek Kanopan. Promotion is done through socialization, brochures, banners, and social media to raise public awareness.